WANPRESTASI ANGGOTA CREDIT UNION PADA PERJANJIAN PINJAM MEMINJAM DALAM TINJAUAN HUKUM PERDATA DAN HUKUM EKONOMI SYARIAH - Alfiatur Rahmah; Sukardi Sukardi; Suhardiman Suhardiman (Al-Aqad, 2022)
This study aims to reveal the practice of default by Credit Union members in loan agreements in the Credit Union area of ??Pontianak, West Kalimantan. This is reviewed in Civil Law using the Civil Code (KUH-Perdata) and Sharia Economic Law using the Sharia Economic Law Compilation (KHES). This study uses a qualitative research method with the type of juridical-normative research in which researchers directly go to the field. The data collection technique uses primary data through observation, interviews, documentation, and secondary data obtained through books, journals, articles, and from the Civil Code and KHES, relating to practices that occur in the field. Researchers can conclude that: 1) several members default on the loan agreement; 2) The review of the Civil Code regarding defaults committed by Credit Union members in the loan agreement has been explained in article 1234 of the Civil Code, which if the debtor does not fulfill his promised performance then he can be said to be in default; 3) Review of KHES regarding the broken promises/defaults committed by Credit Union members in the loan agreement according to article 36 of the KHES and getting sanctions which are contained in article 38 of the KHES. The implication of this research finding is to increase legal awareness. Whatever the form of the agreement must lead to a legal relationship. Decisions that have been mutually agreed upon must be carried out with full responsibility following the applicable rules, especially for Credit Union members who have received loans.